2003
DOI: 10.17660/actahortic.2003.609.38
|View full text |Cite
|
Sign up to set email alerts
|

Production of Micropropagated Melon Plantlets Adapted to Saline Environment

Abstract: An experiment was carried out to evaluate the behaviour on salt stress induced by sodium chloride of two melon clones obtained from micropropagation. Since arbuscular mycorrhizal (AM) fungi seem to increase salt tolerance in some crops, at acclimatisation melon plantlets were mycorrhizal with an AM fungus. The root systems of both mycorrhizal and non mycorrhizal plants were exposed to increasing salt concentrations and then placed in distilled water to study the wilting response and the recovery of plants. Obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…For each artichoke hybrid cultivar, all morphological parameters studied were significantly increased by mycorrhizal symbiosis in agreement with previous research (Ruta et al, 2003;Morone Fortunato et al, 2005). Greater root density would form higher surface absorption areas of roots mainly due to external hyphal growth in the soil (Hardie and Leyton, 1981).…”
Section: Articlesupporting
confidence: 90%
See 1 more Smart Citation
“…For each artichoke hybrid cultivar, all morphological parameters studied were significantly increased by mycorrhizal symbiosis in agreement with previous research (Ruta et al, 2003;Morone Fortunato et al, 2005). Greater root density would form higher surface absorption areas of roots mainly due to external hyphal growth in the soil (Hardie and Leyton, 1981).…”
Section: Articlesupporting
confidence: 90%
“…The effectiveness of the mycorrhizal inoculation has been assessed for many other vegetable species such as leek (Hamel et al, 1997), pea (Bethlenfalvay et al, 1997), strawberry (Taylor and Harrier, 2001), lettuce and onion (Cantrell and Lindermann, 2001), asparagus (Matsubara et al, 1996), mint (Gupta et al, 2002), melon (Ruta et al, 2003), pepper (Estrada-Luna and Davies, 2003;Sensoy et al, 2007), fennel (Kapoor et al, 2004), broad bean (Rabie and Almandini, 2005), basil (Copetta et al, 2007), tomato (Al-Karaki, 2006;Hajiboland et al, 2010), zucchini plants (Colla et al, 2008), watermelon (Westphal et al, 2008) and bean (Pelaez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…inodorus, Origanum vulgare L. subsp. hirtum and Spartium junceum L. plants were multiplied and rooted in vitro in appropriate media (Ruta et al, 2003;Cicco et al, 2004;Morone Fortunato et al, 2005, 2006. After in vitro rooting, the plantlets were transferred to the greenhouse for acclimatization.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown AM efficiency in increasing plant tolerance to salinity related to horticultural crops (Hirrel and Gerdemann, 1980;Copeman et al, 1996;Al-Karaki, 2000;Ruiz-Lozano and Azcón, 2000;Ruta et al, 2003).…”
Section: Introductionmentioning
confidence: 99%